Industries building system for school at Sekolah Menengah Beris Panchor 2 / Muhammad Firdaus Zakaria @ Ibrahim - Zakaria @ Ibrahim, Muhammad Firdaus (Universiti Teknologi Mara, Perak, 2016)
This report is to present the system IBS in use for this building. It use the precast concrete for the structural this building. IBS can cut the cost and can short the period to finish the project. IBS is new in the Malaysia than the bigger country. Have many advantages use this system. It is because can decrease the worker in the site but must use crane to lift the precast concrete. This building use the light weight block for the wall. It is can short time to finish the project. Wall for this building do not load bearing wall. This report is based on my experience during practical training in the site.